Resiliensi Orang Tua yang Memiliki Anak Disabilitas Intelektual: Literature Review - Jackrine Jackrine; Luh Kadek Pande Ary Susilawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Having a child with an intellectual disability requires parents to face greater challenges in parenting, encompassing not only physical needs but also emotional and social aspects. This study aims to explore the resilience of parents of children with intellectual disabilities and the factors that influence it. Parental resilience encompasses the ability to survive, adapt, and thrive despite facing high levels of psychological stress. This study used a narrative literature review method, reviewing 11 international and national journal articles published between 2015 and 2025. The results indicate that psychological stress, such as anxiety, stress, and frustration, is often experienced by parents, but high resilience can mitigate the negative impact of this stress. Factors influencing resilience include the individual characteristics of parents, the characteristics of children with intellectual disabilities, and social and environmental support. Good resilience not only supports child development but also the well-being of parents. Based on these findings, this study suggests the importance of social support and the formation of a community of parents to share experiences and provide emotional support.